TRANSCULTURATION AND AFFECT IN THE L2 CLASSROOM: TEACHING ENGLISH AND ETHNOGRAPHY IN THE YUCATAN - Logan, Joy (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract By offering a transdisciplinary analysis of the development of an EFL/ethnography program in Mexico, this study proposes transculturation, as opposed to acculturation (a process commonly cited by applied linguists), as a more comprehensive conceptual tool for understanding the learning dynamics of the L2 classroom. SELT, School of Experimental Language Training, in the Maya community of Pisté, Yucatán, (Mexico) was a program that sought to teach English to local Pisteleños and to train U.S. university students both in EFL methods and in the practice of cultural ethnography. This study discusses SELT and its uses of Spanish, English and Yucatec Maya in terms of the dynamics of power and authority in the EFL classroom. In comparing the EFL and ethnographic practices employed by SELT, the study explains how transculturation, a concept derived from sociology, anthropology and literary criticism, accounts for multi-directional communication and learning in the L2 classroom. It also suggests affect to be one of the principal components in the transdisciplinary evocation of transculturation.